Talk to me, part 2 ELIZA. IN The Working Programmer. - Neward, Ted.
Ted Neward builds on the example in his last column with a side trip into artificial intelligence. Read on as he uses F# to create Feliza, a chatterbot based on ELIZA.
Keywords: F#.; Chatterbot; ELIZA